Dermatomyositis-like Eruptions, Hydroxyurea-Associated Squamous Dysplasia, and Nonmelanoma Skin Cancer: A Case Report and Systematic Review - Giorgia Di Marco; Gianmarco Diego Bigotto; Eleonora Cossar; Nathalie Rizzo; Stefania Guida; Franco Rongioletti (Dermatopathology)
Hydroxyurea (HU), a cornerstone treatment for myeloproliferative disorders, is associated with a wide range of cutaneous side effects, from xerosis and hyperpigmentation to more severe conditions like dermatomyositis-like eruptions (DM-LE) and nonmelanoma skin cancers (NMSC), particularly squamous cell carcinoma (SCC). In this review, we present a unique case of HU-induced DM-LE with histological evidence of keratinocyte dysplasia and p53 overexpression, followed by a systematic analysis of similar cases. Our findings reveal that the clinical presentation of DM-LE, while typically considered benign, shares clinical and histological features with hydroxyurea-associated squamous dysplasia (HUSD), a precancerous condition that may progress to SCC in chronically exposed patients. Key insights include the characteristic histopathological findings of DM-LE, the role of chronic HU therapy and UV-induced damage in promoting p53 overexpression, and the overlap between DM-LE and HUSD. Regular dermatologic monitoring, patient education on photoprotection, and the careful assessment of skin lesions in long-term HU users are essential for the early detection and prevention of malignancies. This review underscores the importance of distinguishing between DM-LE, HUSD, and SCC to optimize management and minimize risks associated with HU therapy.